Effectiveness of the Free Healthcare Service Policy in Improving Accessibility to Primary Health Services in Gianyar Regency - Putu Gede Pebriantara; Ida Ayu Putu Sri Widnyani; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research aims to evaluate the effectiveness of the free healthcare policy implemented by the Gianyar Regency Government in improving access to primary healthcare services for the community. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and document analysis. The results show that the policy has a positive impact, leading to an increase in visits to community health centers, higher immunization coverage rates, and a decrease in complaints about medical costs. However, challenges remain in the availability of medical staff, the distribution of medicine, and the quality of services. The policy is considered effective, but it requires strengthening in its management and continuous evaluation.